1978
DOI: 10.1073/pnas.75.9.4573
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Z-Pro-D-Leu of development of tolerance to and physical dependence on morphine in mice.

Abstract: The peptide Z-Pro-D-Leu, injected daily in mice receiving morphine chronically, was found to prevent development of physical dependence as measured by changes in body temperature and body weight due either to abrupt or to naloxone-induced withdrawal. On the other hand, administration of Z-Pro-D-Leu only on the last day of morphine treatment did not alter the overt signs of withdrawal. Daily administration of Z-Pro-D-Leu was also effective in blocking the development of tolerance to the analgesic and the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
1

Year Published

1979
1979
1984
1984

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
3
10
1
Order By: Relevance
“…These data are also consistent with work in mice with MIF and cyclo (Leu-Gly) and with another analogue of MIF, Z-Pro-D-Leu (Walter et al, 1978).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data are also consistent with work in mice with MIF and cyclo (Leu-Gly) and with another analogue of MIF, Z-Pro-D-Leu (Walter et al, 1978).…”
Section: Discussionsupporting
confidence: 81%
“…Additional studies (van Ree & de Wied, 1976) indicated that not only DG-AVP, but oxytocin and its C-terminal tripeptide prolylleucyl-glycinamide (MIF) and cyclo (Leu-Gly) facilitated morphine dependence (as measured by the loss of body weight following naloxone administration to dependent rats) as well as development of tolerance to the analgesic effect of morphine. Other studies, however, indicate that oxytocin and vasopressin (Schmidt, Holaday, Loh & Way, 1978) and cyclo (Leu-Gly) (Bhargava, 1980a) Previous studies have demonstrated that an analogue of MIF, Z-Pro-D-Leu, (Walter, Ritzmann, Bhargava, Rainbow, Flexner & Krivoy, 1978), MIF and cyclo (Leu-Gly) (Walter, Ritzmann, Bhargava & Flexner, 1979; inhibit the development of tolerance to and physical dependence on morphine in mice. Additionally, it was found that cyclo (Leu-Gly) also inhibited morphine tolerance in the rat (Bhargava, 1980b).…”
Section: Introductionmentioning
confidence: 99%
“…Although we obtained similar results in mice in the case of oxytocin (unpublished data) with the method of morphine implantation as described (1,2), the current results with MIF and cyclo(Leu-Gly) in mice are apparently in disagreement with those reported by van Ree and de Wied (13) for these compounds in rats. The disparity between the two studies may be due to differences of species, routes of morphine administration, or doses used.…”
Section: Resultscontrasting
confidence: 56%
“…Recent evidence (1) indicates that the dipeptide benzyloxycarbonyl-Pro-D-Leu is capable of blocking the development of tolerance to and physical dependence on morphine in mice; these effects were achieved without altering the analgesic potency of morphine.…”
mentioning
confidence: 99%
See 1 more Smart Citation